Utilization Of Origami As A Learning Strategy In Improving Students' Numeracy Skills - Indrawatiningsih, Nonik; Amala, Ayyukum Akhsanu; Saskiyah, Bela Alimatus; Nuzula, Shafalma Firdaus; Rohmah, Silatur (IndoMath: Indonesia Mathematics Education, 2024)
Based on scientific studies that have been conducted, data shows that the achievement of Indonesian students in the numeracy aspect is low. This study aims to improve students' numeracy skills through the utilization of origami paper media in the learning process. The type of research is descriptive qualitative. The subjects in this study were 5th grade students at SDN Alastlogo 1 Lekok, Pasuruan Regency, totaling 25 people. The instruments used were the Minimum Competency Assessment (AKM) pretest and posttest sheets and field notes. The source of data in this study came from the results of the pretest and posttest of the Minimum Competency Assessment (AKM Class). The data collection technique used is to carry out the AKM Pretest. Then make a learning strategy for flat building material using origami media to students. After that, the Class AKM Posttest was conducted as a student evaluation. The data analysis technique used is comparative analysis. In addition, analyzing each learning process using folding paper or origami media, to determine the effectiveness of learning implemented in the study. The results of this study show that there is an increase in students' numeracy skills by 80%. Students can answer correctly from the flat building questions tested on the AKM Posttest, whereas previously in the AKM Pretest, only 20% of students could answer correctly. This proves that folding paper or origami media is very effective to help improve students' numeracy skills regarding flat shapes.